2016
DOI: 10.1097/sla.0000000000001615
|View full text |Cite
|
Sign up to set email alerts
|

Hold the Pendulum

Abstract: Objective To determine whether restrictive fluid resuscitation results in increased rates of acute kidney injury (AKI) or infectious complications. Summary Background Data Studies demonstrate that patients often receive volumes in excess of those predicted by the Parkland equation, with potentially detrimental sequelae. However, the consequences of under-resuscitation are not well-studied. Methods Data were collected from a multicenter prospective cohort study. Adults with greater than 20% total burned sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
5
1
Order By: Relevance
“…It has previously been believed that restrictive resuscitation is associated with increased AKI. However, analysis of urine in this study did not confirm these beliefs 27…”
Section: Discussioncontrasting
confidence: 81%
“…It has previously been believed that restrictive resuscitation is associated with increased AKI. However, analysis of urine in this study did not confirm these beliefs 27…”
Section: Discussioncontrasting
confidence: 81%
“…Risk of bias is summarized in Supplementary Table 1 of the (cohort or case-control studies) and Supplementary Figure 1 of the (RCT studies). Among the 57 included studies, 22 were from North America ( 4 , 9 , 15 , 16 , 24 , 26 , 28 , 30 , 31 , 33 , 34 , 40 , 42 44 , 48 50 , 54 , 59 , 61 , 62 ), 18 were from Asia ( 5 , 7 , 19 , 21 23 , 25 , 36 38 , 41 , 46 , 47 , 51 , 52 , 58 , 64 , 67 ), 15 were from European countries ( 6 , 17 , 18 , 20 , 27 , 32 , 35 , 45 , 53 , 55 57 , 60 , 65 , 66 ), one was from South America ( 29 ), one was Africa ( 39 ). A total of 12 studies could not be used for analysis of the prevalence of RRT, seven of which only reported on RRT patients ( 9 , 18 , 34 , 37 , 38 , 43 , 45 ), four of which were RCT studies ( 40 , 41 , 51 ,…”
Section: Resultsmentioning
confidence: 99%
“…Optimization of resuscitation protocols revealed the importance of rapid initiation, the complications induced by delayed resuscitation, the perils of over- and under-resuscitation, the benefits of guided fluid administration, utility of enteral resuscitation (especially for mass disaster scenarios), and considerations for special populations (e.g. pediatrics, pregnancy) (2, 48). Characterization of the hyperdynamic phase occurring 2–3 days post-burn showed low systemic vascular resistance, elevated cardiac output, systolic dysfunction, and increased myocardial energy demand (5, 9).…”
Section: Resuscitationmentioning
confidence: 99%